Factors and comparative analysis of COVID-19’s impact on household food security in rural and urban regions. - Utoro, Panggulu Ahmad Ramadhani; Pujokaroni, Agustu Sholeh; Aini, Qurratu; Saragih, Bernatal (Nutrición Clínica y Dietética Hospitalaria, 2025)
Introduction: The COVID-19 pandemic has significantly affected household food security in Indonesia, particularly in both rural and urban areas. This study compares food security between rural and urban households during the pandemic. This study aims to compare food security between rural (Paser Regency) and urban (Balikpapan City) households during the pandemic. Methods: Using a cross-sectional design, 300 households were sampled (150 each from Balikpapan and Paser), with data collected through interviews and questionnaires. Household income, food, and non-food expenditure were analyzed using descriptive statistics and Pearson correlation with IBM SPSS Statistics 24. Result: The results show that increased food (r = 0.230, p < 0.01) and non-food (r = 0.113, p < 0.05) expenditure are positively correlated with food security. In Balikpapan, 18% of households saw a decrease in food expenditure compared to 11% in Paser, while non-food spending increased in 41.3% of Balikpapan households compared to 36% in Paser. Social assistance also had a positive impact (r = 0.149, p < 0.01), with 61.3% of households in Paser receiving aid compared to 51.3% in Balikpapan. Spending on staple foods like vegetables and proteins also contributed to food security (r = 0.126, p < 0.05). Mothers in Balikpapan were more concerned about food availability (71.3%) than in Paser (69.3%). Conclusion: Balikpapan faced more severe financial impacts and household concerns during the pandemic, while Paser showed greater stability. Key factors influencing food security included increased spending on food and non-food items, health concerns, and the effectiveness of social assistance in both regions.